Deteksi Gerak Menggunakan Kamera Pada Raspberry Pi Dengan Penyimpanan Data Cloud Storage - Valdo Franata; Erwin Setyo Nugroho; Yuli Fitrisia (UIN Sultan Syarif Kasim Riau, 2015)
Crime that happen anytime and anywhere requires a monitoring system to monitoring theincident. Continuous monitoring would cost media storage, because recorded video will has big size. Oneway to overcome this problem is to build a system using a webcam to record necessary moment. Forinstance is when there was a movement in a moment/event. Therefore, a monitoring system that candetect any movement in a room is needed. In this study, the problem can be solved by designingmonitoring system based Raspberry Pi. This monitoring system is created using Motion program. Motionprogram handles motion detection and stream captured by camera, otherwise the system can also send anotification when motion is detected via e-mail and upload recorded video to DropBox. In Testing processis with different lighting conditions and distance, the system has worked 100% in bright light. In the dimlight at distance of 4 meters has 95% success rate and 83.3% at a distance of 6 meters, and in the darkwithout light illumination has 0% success rate. Motion detection process is strongly influenced by lightintensity in the room.Keywords: DropBox, Motion Detection , Motion, Raspberry Pi, Webcam